THE RELASIONSHIP BETWEEN COMPANIES’ EARNINGS PER SHARE (EPS) AND GEARING - Nazruzila Razniza Mohd Nadzri; Mary Mathews; Dihlvinder Kaur Mohkam Singh; Kalaveny Kanagasingam (Journal of Islamic, Social, Economics and Development, 2022)
The objective of the study is to calculate and measure gearing ratios and EPS (Earning Per Share) of public listed companies and to examine the relationship between the debts and EPS. The study was empirical in nature. The study was conducted over a period of 5 years for the financial years 2016 to 2020 and is based on secondary sources of data. Gering ratios were calculated from the information given in the financial position of the companies and the EPS is based on the value given in the balance sheet of the respective companies. Excel was used to determine the correlation between EPS and the debt ratio. It was concluded that there is moderate correlation between gearing (debt) and EPS. The correlation coefficient is greater than zero, therefore, it can be concluded that it is a positive relationship.